Tingkat Pengetahuan Karang Gigi Dan Status Kebersihan Gigi Dan Mulut Ibu Rumah Tangga Di Pedesaan - Shelma Adelia; Dwi Suyatmi; Etty Yuniarly (Journal of Oral Health Care, 2017)
Knowledge closely connected with the attitude of a person about the disease and prevention efforts. Lack of knowledge about health is a predisposing factors of health behavior that lead to outbreaks of disease. The lack of knowledge about the health of the teeth and mouth will affect the appearance of the coral reef teeth. This research aims to know the description of the level of knowledge of the coral reef the teeth and the the level of dental hygiene at the mouth of the mother - housewife in the village are Ngawen Pancurwening Wonosobo. This research is a descriptive with the design of the cross sectional research. The sample consists of all housewives RT 02 villages are Ngawen Pancurwening Wonosobo which numbered 35 respondents with saturated sampling techniques. Research data obtained by direct observation and questionnaire. Checking the the level of dental hygiene and mouth using the appliance oral diagnostic. The level of the cleanliness of the teeth and mouth using the index good/medium/bad based on Green And Vermilion, data analysis presented in the form of cross-tabulation. The results of the study showed that most of the characteristics of the research subjects as much as 91,4% have the level of knowledge that "good" , the the level of dental hygiene and the mouth of the highest with the criteria are as much as 65,7%. From the results of the study showed the majority of respondents with knowledge level of "good" owned by age group of mothers adult household as much as 71,4%, Most respondents have the the level of dental hygiene and the mouth of "medium" owned by age group adult 51.4%, and respondents with knowledge level of "good" with the the level of dental hygiene and the mouth of "medium" as much as 65,6%. The conclusion of this research are the majority of the mothers house in the village are Ngawen Pancurwening Wonosobo have knowledge level that "good" with the the level of dental hygiene and the mouth of "medium".